Iceshock Swarms Observed at Mizuho Camp, Antarctica - Katsutada KAMINUMA; Masayoshi TAKAHASHI (National Institute of Polar Research, 1975)
The wintering party of the 14th Japanese Antarctic Research Expedition carried out a temporary seismological observation with one vertical component seismograph at the Mizuho Camp on September 10-27, 1973. The Mizuho Camp is located at about 300km southeast of Syowa Station in Antarctica, where the ice thickness is about 2,100 m. The seismological observation was disturbed by the ground noise of many kinds of artificial origin, but good records for 210 hours in total were obtained. Natural earthquakes were not detected by this temporary observation, but many iceshocks, mostly of swarm type, were recorded. These swarms occurred in the nighttime. The air temperature during the iceshocks was below -35℃, and the falling rate of temperature was -2.5℃ per hour for a short period, or about -1℃/hour though the lowering continued for a few hours. When the largest swarm during this observation period occurred, the wintering members at the Mizuho Camp heard sound from shocks and recognized many cracks on the snow surface around the area of the sound. Therefore, the depth of the swarm was estimated to be very shallow. Some shocks were interpreted to have been originated from the upper snow layers quite near the surface, so they may be called snowquakes.